The Realization of Apology Strategies: A Comparative Study between Moroccan EFL Learners and Native Speakers of English - JARRAR, Abdelhay; Kerouad, Smail; Masmoudi , Imane (International Journal of Language and Literary Studies, 2022)
Pragmatic competence, generally defined as the study of language in its social context, has been part and parcel of language learning and teaching. Oftentimes, second language learners tend to fall short in expressing themselves in spite of their linguistic competence. Second language pragmatic research has shown that the greater the difference between cultures, the greater the likelihood of pragmatic failure among non-native speakers of English. With this in mind, this study aims at comparing the similarities and differences between Moroccan University Learners of English (MLE) and Native Speakers of English (NSE) apology strategies in order to identify and predict aspect of language use which are likely to create intercultural communication breakdowns among the two cultures, thus contributing to foreign language education. Henceforth, using a discourse completion task, data was elicited from 50 MLE and 50 NSE, who responded to 8 apology situations. Results showed that the most frequent strategy used for both groups is the explicit Illocutionary Force Indicating Device (IFID); however, the two groups differ in the frequency of other implicit apology strategies.